PENGARUH MODEL PEMBELAJARAN AIR BERBANTU MEDIA LAGU MATERI ALJABAR TERHADAP KEMAMPUAN PEMAHAMAN KONSEP - Nur Latifah; Nur Baiti Nasution (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2024)
The purpose of this study was to analyze and improve the concept understanding abilities of class VII students using the AIR learning model assisted by algebra song. This research uses a type of experimental research with a one group pretest-posttest design. This type of experimental research is included in quantitative research methods. The sampling technique uses cluster random sampling technique. The instrument for collecting data in this research is a test instrument in the form of pretest and posttest questions. All students in class VII F were given pretest questions on real numbers and their operations. At the next 2 meetings, treatment was given in the form of learning algebra material using the AIR learning model assisted by algebra song. After the treatment was carried out, posttest questions on algebra material were given to students. Next, analysis of all data is carried out using the following steps: analysis of initial and final data, data presentation stage, and conclusions. The results of the research show that there is an increase in students' ability to understand concepts by using the AIR learning model assisted by algebra song media. The use of the AIR learning model assisted by algebra song is said to be significant in improving the ability to understand concepts because the proportion of students after being given the AIR learning model assisted by algebra song who completed it exceeded the KKM score (>70) of more than 75% of the total number of students